POTENSI DAN TANTANGAN PENGEMBANGAN INDUSTRI MICE DI SULAWESI UTARA: ANALISIS DAYA SAING DESTINASI - Bet El Silisna Lagarense; Tedy Valens Silape; Sri Martini; Jelly Netty Sendow (Jurnal Hospitaliti, 2025)
The MICE (Meeting, Incentive, Convention, and Exhibition) industry has become a strategic tourism segment in driving regional economic growth. This research aims to analyze the potential and challenges of MICE industry development in North Sulawesi and examine destination competitiveness within the context of national and regional MICE markets. North Sulawesi possesses geographical advantages as the gateway to Eastern Indonesia, supported by adequate hotel infrastructure and international accessibility through Sam Ratulangi International Airport. However, MICE development in this region still faces various challenges including limited large-capacity convention venues, suboptimal stakeholder coordination, and restricted destination promotion. Employing a qualitative descriptive analysis approach and destination competitiveness assessment, this research identifies key factors affecting MICE development in North Sulawesi. The findings indicate that although North Sulawesi has significant potential in tourism attractions, culture, and regional connectivity, a comprehensive development strategy is required encompassing MICE infrastructure enhancement, human resource capacity building, and synergy among government, hospitality industry, and business operators. This research is expected to provide strategic recommendations for sustainable MICE industry development in North Sulawesi.